THE EFFECTIVENESS OF INDEX CARD MATCH TO PRACTICE ANALYSIS AND EVALUATION THINKING SKILLS ON VIRUS MATERIAL FOR SENIOR HIGH SCHOOL GRADE 1 - Yuktika, Siti; Susantini, Endang (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
The analysis and evaluation thinking skills should be trained to learners in entering the 21st century. Skills could be trained through various ways in learning activities, including the application of media in learning. Learning media was used to facilitate learners in understanding learning materials and to solve a problem. Index Card Match was a learning media in the form of cards that contain important concepts of a learning material. The card consisted of a question sheet and an answer sheet. Index Card Match developed on virus material. Virus material included the structure, replication, and role of the virus in life. The development of Index Card Match used ASSURE development methods. Effectiveness data was obtained by using the one group pretest and posttest design. The pretest and posttest results were analyzed using the method of the gain score. This research aimed to describe the effectiveness of media Index Card Match to practice the thinking skills of analysis and evaluation on virus material of X class. The research activities were conducted in the Biology Department, Mathematics and Natural Science Faculty, Universitas Negeri Surabaya. A limited trial was conducted on 15 students at SMAN 3 Tuban. The results of this research showed that the media Index Card Match was very effective based on the acquisition of the increased mastery test results 100% (very effective), as well as the thinking skills of analysis and evaluation were increasingly high with acquisition gain score 0.71. Based on these results the media Index Card Match developed in virus material was effective to practice analysis and evaluation thinking skills. Keywords: Index Card Match, analysis and evaluation thinking skills, virus material.